2018
DOI: 10.1186/s12909-018-1341-9
|View full text |Cite
|
Sign up to set email alerts
|

Experiential education enhancing paramedic perspective and interpersonal communication with older patients: a controlled study

Abstract: BackgroundParamedics are required to provide care to an aging population with multidimensional and complex issues. As such educators need to prepare undergraduate paramedics to recognise, assess and manage a broad range of psychosocial care and support issues beyond somatic conditions. Experiential educational interventions with older people provide realistic and contextualised experience which can improve the provision of holistic patient focused care.MethodsThis was a single institution controlled before-aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
(36 reference statements)
1
10
0
Order By: Relevance
“…Self-reflection demonstrated further improvements in the students’ learning. Results also demonstrated an increase in the students confidence and empathy levels, which was further reflected in the work by Ross et al ( 2018 ). In this study, communication skills improved in all students who practiced communicating with an older person, however those who had more one on one time, developed more empathy towards this patient group.…”
Section: Presentation Of Resultssupporting
confidence: 78%
“…Self-reflection demonstrated further improvements in the students’ learning. Results also demonstrated an increase in the students confidence and empathy levels, which was further reflected in the work by Ross et al ( 2018 ). In this study, communication skills improved in all students who practiced communicating with an older person, however those who had more one on one time, developed more empathy towards this patient group.…”
Section: Presentation Of Resultssupporting
confidence: 78%
“…A mixed‐methodology study identified that exposure to older groups improved student paramedic confidence when communicating with older patients (Ross & Williams, 2014). This study was later supported by a controlled trial (n = 124) that identified that student paramedics who received a geriatric educational program demonstrated better communication with older patients than those who did not receive this training (Ross et al, 2018).…”
Section: Methodsmentioning
confidence: 93%
“…These included cancer, dementia, elderly, and pediatric patients (Credland, Hurwood, & McKenzie, 2020; Drewitz‐Chesney, 2019; Noack, Kleinert, & Muller, 2020). Two articles by Ross et al (Ross, Jennings, Gosling, & Williams, 2018; Ross & Williams, 2014) investigated student paramedic communication with older patients. A mixed‐methodology study identified that exposure to older groups improved student paramedic confidence when communicating with older patients (Ross & Williams, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, teaching and learning must be tailored to meet the emerging demands of effective clinical practice. Experiential learning is essential for enhancing the relational and psychomotor skills development in health care students because of the intricacy of health-illness phenomena and the uncertainties associated with health care students (3,4). Experiential learning refers to learning by doing and entails hands on experiences.…”
Section: Introductionmentioning
confidence: 99%